Molecular Orientation and the Performance of Synthetic Oolymeric Membranes for Gas Separation - Shilton, S. J.; Ismail, A. F.; Gough, P. J.; Dunkin, I. R.; Gallivan, S. L. (Elsevier, 1997)
Asymmetric polysulfone and polyacrylonitrile flat sheet membranes have been produced by a simple drywet casting technique. Both membrane types were cast at low and high shear rate. Molecular orientation in the membranes was determined using polarized reflection i.r. spectroscopy. Gas permeation properties were examined using carbon dioxide and methane as test gases. I.r. dichroism was detected in all samples, the extent being greater in the high shear membranes for both polysulfone and polyacrylonitrile. The effects, however, were more intense in the polyacrylonitrile samples. Gas permeation tests showed that for both polymer types, the high shear membranes exhibited greater selectivity (CO2/CH4). Selectivities were greater and permeabilities lower for the polysulfone samples. The results show (i) that polarized reflection i.r. spectroscopy can be used to determine at least qualitatively the degree of molecular orientation in sheared polymers, (ii) that molecular orientation is enhanced by shear during casting, and (iii) that this has a favourable effect on membrane selectivity. In the examples chosen molecular orientation was more pronounced in the polyacrylonitrile membranes, but with these the potential for high selectivity was thwarted by the poor intrinsic permeability of the polymer which causes flow through pores or imperfections to dominate.